Teknik Komunikasi Aplikasi Buddyku Memanfaatkan Platform Media Sosial Instagram untuk Menampilkan Materi Berita - Benjamin Nicolas Sinaga; Farid Rusdi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The importance of strategic communication in promoting new innovative apps like BuddyKu is a common topic in social media and marketing strategies. BuddyKu is an app that allows content creators to post content on any topic on their platform. Once the page/user profile is created, the user can comment on articles and post videos, posters, articles and photos. This app is made for young creators to improve their content creation skills to be posted publicly, but BuddyKu promotes it on Instagram. The page has reached 15,000 plus followers and is also a verified account on Instagram. This makes BuddyKu known to the public by posting reels (short videos), articles and posters. The importance of strategic communication in promoting new innovative apps like BuddyKu is a common topic in social media and marketing strategies. BuddyKu is an app that allows content creators to post content on any topic on their platform. Once the page/user profile is created, the user can comment on articles and post videos, posters, articles and photos. This app is made for young creators to improve their content creation skills to be posted publicly, but BuddyKu promotes it on Instagram. The page has reached 15,000 plus followers and is also a verified account on Instagram. This makes BuddyKu known to the public by posting reels (short videos), articles and posters.